2023
DOI: 10.31729/jnma.8085
|View full text |Cite
|
Sign up to set email alerts
|

Hernia among Patients Admitted to the Department of Surgery of a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Hernia is one of the most common surgery-requiring conditions. Despite this, hernia still needs to be studied in more detail. The main objective of the study was to find out the prevalence of hernia among patients admitted to the Department of Surgery of a tertiary care centre. Methods: A descriptive cross-sectional study was conducted among patients admitted to the Department of Surgery of a tertiary care centre from 1 July 2021 to 31 December 2022. Ethical approval was obtained from the Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…8 In our study, the hernia was almost 3 times more common in males than females which was in coherence with other studies in which there were 63.4% males and 36.6% females, 9 79.2% males and 20.8% female, 11 86.54% males and 13.45% females. 6 Inguinal, umbilical, epigastric hernia, and supraumbilical hernia showed male preponderance whereas incisional hernia was more common in females, the femoral hernia was seen only in females which were in coherence with the findings of another study in which the male: female ratio was 23.95:1 for inguinal hernia, 1.78:1 for umbilical hernia, and 2.77:1 for an epigastric hernia. 6 The mean age of the hernia patients was 42.76±21.85 years with the distribution of hernia increasing with age, peaking at age 40-59 years, then falling gradually.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…8 In our study, the hernia was almost 3 times more common in males than females which was in coherence with other studies in which there were 63.4% males and 36.6% females, 9 79.2% males and 20.8% female, 11 86.54% males and 13.45% females. 6 Inguinal, umbilical, epigastric hernia, and supraumbilical hernia showed male preponderance whereas incisional hernia was more common in females, the femoral hernia was seen only in females which were in coherence with the findings of another study in which the male: female ratio was 23.95:1 for inguinal hernia, 1.78:1 for umbilical hernia, and 2.77:1 for an epigastric hernia. 6 The mean age of the hernia patients was 42.76±21.85 years with the distribution of hernia increasing with age, peaking at age 40-59 years, then falling gradually.…”
Section: Discussionsupporting
confidence: 81%
“… 5 Another study at the National Academy of Medical Sciences in Kathmandu found a greater prevalence of hernias (23.14%) than in our study. 6 Saudi Arabian people had a hernia prevalence of 11.7%, 7 whereas Central Russians had a hernia prevalence of 20.9%. 8 A tertiary care centre in India reported a 22% burden of abdominal hernia among patients who had been admitted.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations